2018
DOI: 10.1155/2018/9840862
|View full text |Cite
|
Sign up to set email alerts
|

MHD Mixed Convection Micropolar Fluid Flow through a Rectangular Duct

Abstract: Mixed convection flow through a rectangular duct with at least one of the sides of the walls of the rectangle being isothermal under the influence of transversely applied magnetic field has been analyzed numerically in this study. The governing differential equations of the problem have been transformed into a system of nondimensional differential equations and then solved numerically. The dimensionless velocity, microrotation components, and temperature profiles are displayed graphically showing the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Also, it is observed that the fluid rotates in the negative y-direction at the left region of the duct. But in the right region, it rotates about the positive y-direction [13,16]. Figure 2e presents the maximum magnitude of temperature along x-axis at the center of the left vertical wall and decreasing at the center of the duct, it increases by a smaller rate when approaching to the center of the right vertical wall, while the maximum value of temperature along y-axis at the center and the rate is decreased when it is near to the horizontal walls.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Also, it is observed that the fluid rotates in the negative y-direction at the left region of the duct. But in the right region, it rotates about the positive y-direction [13,16]. Figure 2e presents the maximum magnitude of temperature along x-axis at the center of the left vertical wall and decreasing at the center of the duct, it increases by a smaller rate when approaching to the center of the right vertical wall, while the maximum value of temperature along y-axis at the center and the rate is decreased when it is near to the horizontal walls.…”
Section: Resultsmentioning
confidence: 96%
“…Janardhana et al [15] investigated numerically the thermal radiation heat transfer effect on the unsteady MHD flow of micropolar fluid over a uniformly heated vertical hollow cylinder using Bejan's heat function concept. Ayano et al [16] investigated numerically of mixed convection flow through a rectangular duct under the transversely applied magnetic field with at least one of the sidewalls of the duct being isothermal, the governing differential equations have been transformed into a system of nondimensional differential equations and are solved numerically such as the velocity, temperature, and microrotation component profiles are displayed graphically. Miroshnichenko et al [17] investigated numerically the laminar mixed convection of micropolar fluid through a horizontal wavy channel by the finite difference method, they solved the system of equations of dimensionless stream function, vorticity and temperature then, studied the effects of Reynolds, Rayleigh, Prandtl numbers, vortex viscosity parameter and undulation number onto streamlines, isotherms, vorticity isolines as well as horizontal velocity and temperature profiles.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the gradual increase of thermal radiation parameter caused a decline in the velocity pro le. MHD mixed convection micropolar uid ow through a rectangular duct was studied by Ayano et al [15], and they observed that the ow reversal increased and velocity decreased as the magnetic eld was intensi ed. Roy and Gorla [16] analyzed the time-dependent MHD micropolar uid past a wedge, and explored that the magnetic eld parameter considerably a ected the amplitude of the drag coe cient.…”
Section: Introductionmentioning
confidence: 99%
“…For some of these fluids the unresolved rotatory motion arises from the asymmetric shape of their molecules, but for others it is an eddying motion existing on microscales, the molecules themselves being roughly point-like. These unresolved eddies visibly affect the resolved motion, for example leading to an altered resolved viscosity or to enhancement of flows and jets (Peddieson 1972;Chaturani et al 1984;Kirwan Jr. 1986;Siddiqui 2016;Ayano et al 2018).…”
Section: Introductionmentioning
confidence: 99%